2011
DOI: 10.1002/ibd.21560
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the role of fatty acids in the pathogenesis and resolution of inflammatory bowel disease

Abstract: Dietary and endogenously modified lipids modulate inflammation by functioning as intra- and intercellular signaling molecules. Proinflammatory lipid mediators such as the eicosanoids compete against the signaling actions of newly discovered modified fatty acids that act to resolve inflammation. In inflammatory bowel disease, multiple aberrancies in lipid metabolism have been discovered, which shed further light on the pathogenesis of intestinal inflammation. Mechanisms by which lipids modulate inflammation, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
65
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 128 publications
(138 reference statements)
1
65
0
1
Order By: Relevance
“…Thus, there is still an unmet medical need for the innovated approaches for treating IBD patients. In this study, we demonstrate the therapeutic potential of C75, a FASN inhibitor, against a murine model of DSSinduced colitis in terms of attenuating The abnormalities in FA metabolism have been reported in IBD, which can be considered as one of the etiologies for the development of this disease (33). We have demonstrated that FASN expression extends from the top of the crypt in the sham mice to the entire mucosa in the colitis mice, detected by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, there is still an unmet medical need for the innovated approaches for treating IBD patients. In this study, we demonstrate the therapeutic potential of C75, a FASN inhibitor, against a murine model of DSSinduced colitis in terms of attenuating The abnormalities in FA metabolism have been reported in IBD, which can be considered as one of the etiologies for the development of this disease (33). We have demonstrated that FASN expression extends from the top of the crypt in the sham mice to the entire mucosa in the colitis mice, detected by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 55%
“…This study is the first to our knowledge to show a link between PPARg and TFF3. Some fatty acids can promote inflammation, whereas others like CLA can be protective in animal models of IBD (17,(27)(28)(29)(30)(31). This fatty acid has positive health effects in animal models of inflammatory disorders such as atherosclerosis, diabetes, and IBD [reviewed in (32,33)].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may explain how long-chain n-3 PUFAs may influence risk of UC 9 51. First, long-chain n-3 PUFAs acting as a competitive substrate decreases the production of the eicosanoids from arachidonic acid, and reduces membrane levels of leukotriene B4.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, long-chain n-3 PUFAs affect cell membrane structure and inhibit dimerisation and activation of the toll-like receptor 4, which is important in mediating intestinal inflammation 52. In mouse models, administration of n-3 PUFA before induction of colitis appears to protect against the development of colitis 51. Second, dietary long-chain n-3 PUFAs inhibit vascular adhesion molecule expression in contrast to arachidonic acid which increases intercellular adhesion molecule 1 expression 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation